Plasma big‐endothelin levels, cardiac autonomic neuropathy, and cardiac functions in patients with insulin‐dependent diabetes mellitus - Erbas, Tomris (Clin Cardiol, 2009)
Background: The alteration of endothelin (ET) levels in diabetic patients with cardiac autonomic neuropathy (CAN) has not been studied extensively and its correlation with cardiac function parameters has not been discussed. Hypothesis: The aim of the present study was to discuss the correlation between the degree of cardiac autonomic neuropathy, plasma big‐ET levels, and cardiac functions in diabetic patients who were clinically free of cardiovascular disease. Methods: Twenty subjects (32.1 ± 7.8 years, 11 men, 9 women) with insulin‐dependent diabetes mellitus (IDDM) were studied to evaluate the relationship between circulating big‐endothelin (big‐ET1) levels, CAN, and cardiac functions. The severity of CAN was scored according to Ewing's criteria. Cardiac functions were assessed using Doppler echocardiography. Results: Left ventricular systolic function in the patient group was within normal limits and comparable with the values of the control group (n = 10). The mean E/A values of diabetics with CAN (1.15 ± 0.33, p = 0.004) and without CAN (1.34 ± 0.17) were significantly lower than those of controls (1.57 ± 0.27). Diabetics with CAN had significantly higher big‐ET1 values (81.1 ± 94 pg/ml) compared with others (12.4 ± 5.9 and 21.1 ± 17.7 pg/ml, p = 0.04). Circulating big‐ET1 levels showed a significant correlation with E/A values in the control group (p = 0.01, r = ‐ 0.7) and with peak A values (p = 0.003, r = 0.64) in diabetics. The CAN score correlated negatively with E/A values (p = 0.01, r = 0.54). Conclusions: High big‐ET levels might have an important role in the pathogenesis or consequences of diastolic dysfunction in diabetics with CAN. Their role in cardiac autonomic neuropathy and diastolic dysfunction should be investigated further.